Small-signal analysis of 1.3/spl mu/m microcavity light-emitting diodes - HEGARTY, JOHN (My University, 1999)
THE MODULATION SPEED OF 1.3-MU M MICROCAVITY LIGHT-EMITTING DIODES (MCLED'S) HAS BEEN MEASURED USING A SMALL-SIGNAL MODULATION ANALYSIS, A SPEED OF 260 MHZ USING A 25-MU M DIAMETER SAMPLE AT CURRENT DENSITY OF 10 KA/CM(2) HAS BEEN ACHIEVED, THE CARRIER CONFINEMENT HAS BEEN CALCULATED FOR SEVERAL CARRIER DENSITIES IN ORDER TO INVESTIGATE THE ORIGIN OF THE SPEED LIMITATION. BY COMPARING THE PERFORMANCE OF THE 1.3-MU M MCLED'S WITH THAT OF THE 990-NM DEVICES WE CONCLUDE THAT THE LIMITING FACTOR ON THE SPEED SEEMS TO BE A LACK OF CARRIER CONFINEMENT IN THE QUANTUM WELLS AND NOT A CAVITY EFFECT.
PUBLISHED
Keywords: carrier density; current density; infrared sources; light emitting diodes; micro-optics; micromechanical resonators; optical resonators